The Effect of Model Discovery Learning on Students’ Self-Efficacy and Student Learning Outcomes - Rina Febriana; Prihastini Oktasari Putri; Hafizah Delyana (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
One of the factors that influences a person's level of success in the learning process is self-efficacy. Low self-efficacy and student learning outcomes in the learning process are the background for this research. In order for student self-efficacy and learning outcomes to increase, there needs to be a learning process that makes students learn meaningfully, one of which is the model discovery learning. The purpose of writing the article is to see whether there is an increase in student self-efficacy after implementing the discovery learning model and whether there are differences in learning outcomes between the application of the model discovery learning and student learning outcomes using the scientific approach. The method in this research uses experimental research methods with research instruments in the form of questionnaires given to students before and after the learning process using discovery learning models and learning outcomes tests. Based on the calculations, it was found that there is an increase in students' self-efficacy after applying the model discovery learning, with a value of 0.43 categorized as a